FAKTOR-FAKTOR PENYEBAB TERJADINYA PENELANTARAN TERHADAP ORANG TUA YANG DILAKUKAN OLEH ANAK DALAM KAJIAN PASAL 5 UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA (STUDI KASUS PENGHUNI PANTI SOSIAL TRESNA WERDHA BUDI MULIA 2 JELAMBAR TAHUN 2018-2019) - Alan David Arif; Mety Rachmawati (Jurnal Hukum Adigama, 2019)
Many problems occur regarding the negative of parents by their children, intentionally or unintentionally, due to certain factors. Children should look after their parents by sending them to nursing homes, so that they can spend more time with their children. This obligation regulated in the Article 5 of Act/Law No. 23 of 2004 concerning the Elimination of Domestic Violence, thus it is not carried out in the applicable law by the community. The government currently only provides protection for the victims, but does not take action against the perpetrators of neglect. Most people are not aware of the government regulation about neglect of family members, the community also does not provide reports to the authorities in the event of neglect, that leads perpetrators keep increasing every year and not deter for doing it. The author, about this issue using empirical normative research. The object of research is Social Institution Tresna Werdha Budi Mulia 2 Jelambar in the year 2018-2019.